Individual Risk, Country-Level Social Support, and Bullying and Cyberbullying Victimization Among Youths: A Cross-national Study - Deryol, Rustu (Journal of interpersonal violence, 2022)
This study examined the relationships between three life domains?physical health, risky/deviant lifestyle, and psychosocial adjustment?and traditional bullying and cyberbullying victimization among youths in 23 countries.Methods: We first estimated logistic regression models that examined the relationships between indicators of physical health, risky/deviant lifestyle, and psychosocial adjustment using 23 distinct national samples. This analysis also allowed us to observe patterns of similarity and dissimilarity across countries regarding the correlates of for traditional bullying and cyberbullying victimization. Next, we estimated multilevel models of bullying victimization that combined data across 21 countries and estimated the effects of a country-level indicator of quality of human development (IHDI) in interaction with individual-level indicators of physical health, risky/deviant lifestyle, and psychosocial adjustment.Results: There were both cross-country similarities and differences regarding the individual-level correlates of traditional bullying and cyberbullying victimization. Additionally, countries that had relatively greater quality of human development tended to exhibit lower prevalence of traditional and cyberbullying victimization. Finally, country-level quality of human development conditioned relationships between individual level factors and both traditional and cyberbullying victimization.Conclusions: Findings suggest that student-level bullying-prevention programs should address risk/protective factors across three student life domains, with some risk/protective factors seemingly universally relevant. Moreover, cross-level interactions suggest that enhancing country-level quality of human development can also play an important role in youth bullying prevention.